Study on the Water Volume of Erhai Lake in Yunnan Plateau - LI Hongyan (Renmin Zhujiang)
Based on the monitoring results of hydrological factors such as measured discharge,precipitation,evaporation and outflow in the Erhai Lake Basin from 1956 to 2018,this paper calculates the natural water volume of the Erhai Lake by using two related methods,namely the principle of watershed generation and convergence and the water balance,and studies the trend and periodicity of natural water volume in Erhai Lake over the years through the Manner-Kendall method and wavelet analysis method.The results show that:The natural water volume calculated by the two methods in Erhai Lake for many years is relatively close,with the relative error of 0.5%,that is 851.9 million cubic meters,among which the water production in the lake area is -93.2 million cubic meters,and the water volume of the land is 944.9 million cubic meters (north (a)>west (b)>southeast (c)>east (d),accounting for 54.9%,33.2%,6.9%,and 4.9% of the land water volume,respectively);The natural water volume in the Erhai Lake throughout the year,the flood season,and the dry season show a decreasing trend with time,especially in the flood season;There are periodic changes in the water volume around 9,12,21,and 32 a,which led to the trend of rich and dry changes in the natural water volume of Erhai Lake.